Breeding ang Growing: agripreneurs - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This workshop sought to expand the dialogue on entrepenurship in the hiope of filtering out the noise and clearing the fog to allow the "who" and "what works" in entrepeneurship to become obvious. It was a skilfull blend to expert presentations, real life experiences, focus group discussions from which emerged practical suggestions as to how to proceed. In the end participants generally agreed that while business development is an essential catalyst for growth in agriculture, it is not an end in itself. Therefore strategies employed to promote and develop entrepeneurship must be differente from business development and must be clear in objective, targets and actions.